THE INTERNAL CONTROL SYSTEM AS A TOOL FOR ENSURING THE QUALITY OF POULTRY PRODUCTS - OVCHARUK, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Product quality is a key factor determining competitiveness, food safety, and consumer confidence in the agri-food sector. In modern poultry farming, which is characterized by high production intensity, biological sensitivity of livestock, and strict sanitary requirements, ensuring stable and high-quality output requires more than advanced technologies alone. A well-structured and effective internal control system plays a decisive role in maintaining product quality and operational sustainability. The internal control system in poultry production encompasses a set of organizational, economic, accounting, and managerial procedures aimed at monitoring, evaluating, and improving all stages of the production cycle — from feed procurement and animal health management to processing, storage, and distribution of finished products. Such a system enables timely identification of deviations from established standards, prevention of production losses, reduction of operational risks, and assurance of compliance with regulatory, veterinary, and quality requirements. Integration of internal control with accounting and management reporting significantly enhances the transparency and reliability of information used in managerial decision-making. This integration supports effective planning, cost control, performance evaluation, and continuous improvement of production processes. Internal control thus functions not merely as a formal supervisory mechanism, but as a strategic management tool that contributes to quality assurance, risk management, and long-term efficiency of poultry enterprises. The effectiveness of internal control systems can be substantially strengthened through the implementation of digital technologies, automated monitoring systems, standardized control checklists, and regular staff training. These measures enhance process traceability, improve accountability, and support the consistent production of high-quality poultry products. As a result, enterprises with robust internal control systems gain stronger market positions, higher consumer trust, and improved competitiveness in both domestic and international markets.